Analisis Faktor-faktor yang Mempengaruhi Kebijakan Dividen - Melanthon Rumapea; Dimita H.P. Purba (Universitas Islam Bandung, 2019)
The objective of the research was to examine the influence of Profitability Growth and Investment Decision on Dividend Policy with Debt Policy as Moderating variables in manufacture companies listed in BEI (Indonesia Stock Market) in the period of 2012 – 2016. The research used causal research method. The population was 138 manufacture companies listed in BEI in the period of 2012-2016, and 85 of them were used as the samples, taken by using purposive sampling technique. The number of observations that is as much as 425 data analysis is by 5 years observation 85 companies. The data were analyzed by using residual test. The result of this study showed that simultaneously the variables of Profitability, Growth and Investment Decision had influence on Dividend Policy. Partially, Profitability had significant positive influence on Dividend Policy, and Investment Decision had significant positive influence on Dividend Policy. The variables of Debt Policy is moderating variables to explain influence Profitability, Growth and Invsetment Decision) on Dividend Policy.